Short Badminton Service Construction Test in Universitas Islam Riau Penjaskesrek Students - Gazali, Novri; Cendra, Romi (Universitas Negeri Semarang, 2019)
This research aims to develop or modify form test instrument servicing existing badminton short then made a slight improvement in accordance with BWF badminton latest applied. This research method using the methods of research and development or research and development. Research and development instrument validation using validation of content performed by some of the experts (experts judgment) which make a person test and measurement experts and two experts in the sport of badminton. Based on the results of the analysis of the evaluation of the test instrument expert servicing three short badminton declared valid and reliability, so that it can be used as research for students of Penjaskesrek Universitas Islam Riau.